Managerial ownership and market-based performance indicators: extended agency theory - Jusoh Mohd Abdullah, Katmun@Katmon Nooraisah, Ahamad Rapani Nor Hanani, Ismail Khalid (N/A, 2014)
Managerial ownership and market-based performance indicators: extended agency theory by Jusoh Mohd Abdullah, Katmun@Katmon Nooraisah, Ahamad Rapani Nor Hanani, Ismail Khalid,